Wraparound care for youth injured by violence: study protocol for a pilot randomised control trial. Issue 5 (19th May 2015) - Snider, Carolyn; Jiang, Depeng; Logsetty, Sarvesh; Strome, Trevor; Klassen, Terry
Abstract : Introduction: Injury by violence is the fourth cause of death and the leading reason for a youth to visit an emergency department (ED) in Canada. In Winnipeg, 20% of youth who visit an ED with an injury due to violence have a second visit for a subsequent violent injury within 1 year. Youth injured by violence are in a reflective and receptive state of mind, rendering the ED setting appropriate for intervention. Methods and analysis: This protocol describes a wraparound care model delivered by a support worker with lived experience with violence, supported by social workers and links to multiple community partners. Support workers will be on call 24 h a day, 7 days a week in order to start the intervention in the ED and take advantage of the 'teachable moment'. The protocol is of a pilot randomised control trial to assess the feasibility of a randomised control trial designed to assess efficacy. For the pilot trial, we will assess recruitment, treatment fidelity, participant adherence and safety. The intervention arm will receive wraparound care initiated at the time of their visit for injury due to violence. The control arm will receive standard care. We will use an adapted preconsent randomisation methodology. This intervention has been developed using an integrated knowledge translation approach. Discussion: Interventions delivered in the ED for youth injured by violence require an approach that is appropriate for the unique situation the youth are in. Ethics: The University of Manitoba Health Research Ethics Board (HS 16445 (Cohort study) and HS 16444 (WrapAround Care study) granted ethical approval. Trial registration number: NCT01895738.